The Index of Microcirculatory Resistance as a Predictor of Echocardiographic Left Ventricular Performance Recovery in Patients With ST‐Elevation Acute Myocardial Infarction Undergoing Successful Primary Angioplasty. (1st March 2016) - Faustino, Mariana; Baptista, Sérgio Bravo; Freitas, António; Monteiro, Célia; Leal, Paulo; Nédio, Maura; Antunes, Claudia; Abreu, Pedro Farto e; Gil, Victor; Morais, Carlos
Abstract : Background: This study aims to evaluate the relationship between IMR (Index of Microcirculatory Resistance) and the echocardiographic evolution of left ventricular (LV) systolic and diastolic performance after ST‐elevation acute myocardial infarction (STEMI), undergoing primary angioplasty (P‐PCI). Methods: IMR was evaluated immediately after P‐PCI. Echocardiograms were performed within the first 24 hours (Echo1) and at 3 months (Echo2): LV volumes, ejection fraction (LVEF), wall motion score index (WMSI), E/é ratio, global longitudinal strain (GLS), and left atrial volume were measured. Results: Forty STEMI patients were divided in 2 groups according to median IMR: Group 1 (IMR < 26), with less microvascular dysfunction, and Group 2 (IMR > = 26), with more microvascular dysfunction. In Echo1 GLS was significantly better in Group 1 (−14.9 vs. −12.9 in Group 2, P = 0.005). However, there were no significant differences between the two groups in LV systolic volume, LVEF and WMS. Between Echo1 and Echo2, there were significant improvements in LVEF (0.48 ± 0.06 vs. 0.55 ± 0.06, P < 0.0001), GLS (−14.9 ± 1.3 vs. −17.3 ± 7.6, P = 0.001), and E/é ratio (9.3 ± 3.4 vs. 8.2 ± 2.0, P = 0.037) in Group 1, but not in Group 2: LVEF (0.49 ± 0.06 vs. 0.50 ± 0.05, P = 0.47), GLS (−12.9 ± 2.4 vs. −14.4 ± 3.2, P = 0.052), and E/é ratio (8.8 ± 2.4 vs. 10.0 ± 4.7, P = 0.18). WMSI improved significantly more in Group 1 (reduction of −17.1% vs. −6.8% in Group 2, P = 0.015). Conclusion: Lower IMR was associated with better myocardial GLS acutely after STEMI, and with a significantly higher recovery of the LVEF, WMSI, E/E' ratio and GLS, suggesting that IMR is an early marker of cardiac recovery, after acute myocardial infarction. (J Interven Cardiol 2016;29:137–145)